Antibiotic Resistance Genes in Antibiotic-Free Chicken Farms - Yuhong Liu; Michael Dyall-Smith; Marc Marenda; Hang-Wei Hu; Glenn Browning; Helen Billman-Jacobe (MDPI AG, 2020)
Rising concern about the use of antibiotics in food production has resulted in many studies on the occurrence of antibiotic resistance genes (ARGs) in animal-associated bacterial communities. There are few baseline data on the abundance of ARGs on farms where chickens are intensively raised with little or no use of antibiotics. This study used a high-throughput quantitative PCR array to survey two antibiotic-free chicken farms for the occurrence of ARGs and mobile genetic elements known to enhance the spread of ARGs. No antibiotics had been used on the study farms for five years prior to this study. The results provide a baseline for the occurrence of resistance genes in the chicken production system without direct selective pressure.